1978
DOI: 10.1111/j.1469-8137.1978.tb01568.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal Fungi Stimulate Uptake of Soluble and Insoluble Phosphate Fertilizer From a Phosphate‐deficient Soil

Abstract: SUMMARY One crop of clover followed by three crops of ryegrass were infected with several mycorrhizal fungi and grown in sterilized soil which had received soluble phosphate or Nauru rock phosphate. Plant growth responses to mycorrhizal infection were larger in later crops. Glomus tenuis was successfully introduced into soil already infested with the indigenous mycorrhizal fungi, and was the most efficient fungus used at stimulating phosphate uptake. In all four crops, Nauru rock phosphate was available to myc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

1978
1978
2008
2008

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 19 publications
2
36
1
Order By: Relevance
“…Powell & Daniel (1978) found that after four crops, rye· grass and clover plants infected with a double inoculum of G. margarita and G. fasciculatus had retrieved only 17 % of fertiliser phosphate from a soil, while plants inoculated with G. tenuis grew much better but still recovered only 27% of the Harvest number fertiliser phosphate. Data of Abbott & Robson (1977), Mosse (1977), and Powell (l977c) also show that more efficient mycorrhizal fungi merely recover a higher percentage of any phosphate fertiliser applied to soil.…”
Section: Resultsmentioning
confidence: 99%
“…Powell & Daniel (1978) found that after four crops, rye· grass and clover plants infected with a double inoculum of G. margarita and G. fasciculatus had retrieved only 17 % of fertiliser phosphate from a soil, while plants inoculated with G. tenuis grew much better but still recovered only 27% of the Harvest number fertiliser phosphate. Data of Abbott & Robson (1977), Mosse (1977), and Powell (l977c) also show that more efficient mycorrhizal fungi merely recover a higher percentage of any phosphate fertiliser applied to soil.…”
Section: Resultsmentioning
confidence: 99%
“…Pots were arranged in randomised blocks in an open screenhouse during spring and summer and watered from below with tap water. Recovery of fertiliser P from soil by plants was calculated as before (Powell & Daniel 1978b;Powell 1979Powell , 1980 as: P recovery % = Pr-Po X 100, where:…”
Section: Experiments D (Ryegrass With Pelleted Chatham Rise Rock Phospmentioning
confidence: 99%
“…White clover is also invariably infected by the indigenous mycorrhizal fungi present in al1 New Zealand soils (Powell 1976). Large responses to mycorrhizal inoculation of clover have been reported in sterilised and unsterilised soils (Powel1 19n;Crush 1978;Hall 1978;Powell & Daniel 1978a) with and without P fertiliser (Hall 1978;Powell & Daniel 1978b).…”
Section: Introductionmentioning
confidence: 99%
“…Application of phosphate fertilizer to soil, on the contrary, decreases the percentage of infection of roots with AMF (Hayman et al, 1975) and inhibit the ameliorating effect on plant growth (Thomson et al, 1986). The ability of arbuscular mycorrhizas to increase the uptake of P from phosphorus sources of different solubilities has generally been assessed at one or two rates of the particular applied P and comparisons have been based on top yield and P uptake at a particular rate of application (Powell and Daniels, 1978). In most of these studies, the rate of application of the insoluble P sources was inadequate for maximum plant growth (Powell and Daniels, 1978).…”
Section: Introductionmentioning
confidence: 99%